Analisis Usaha Produksi Ubur-Ubur (Studi Kasus: Usaha Produksi Ubur-ubur Milik Bapak Wahyudi di Desa Temajuk) - Ee Zurmansyah; Muhammad Hidayat (PAKIS JOURNAL INSTITUTE, 2023)
Jellyfish is a fishery product used by humans as food and other products. Jellyfish production in Temajuk Village occurs in certain months, and fishermen make it an additional source of income. The purpose of this study is to analyze the investment costs and feasibility of Mr. Wahyudi's business, the largest business in Temajuk Village. A mixed method was used to purposively determine the respondents. The data collection technique used the deep interview method, and then the data were processed using an analysis of total investment, total costs, depreciation costs, gross income, profits, RCR, PPC, FRR, and BCR. The results of this study indicate that the due diligence analysis of Mr. Wahyudi's business is based on an RCR value of 2.7, which means that every capital expenditure of IDR 1 (one rupiah) generates IDR 2.7 (two points seven rupiahs). The PPC value is 40.8, which means that the business belongs to Mr. Wahyudi, it is feasible to continue, and the return on capital is less than two months; the smaller the PPC value, the faster the return on investment. Thus, from the RCR, FRR, and PPC values, Mr. Wahyudi's production business is feasible to continue.